Briefing: Collaborative management for sustainable beaches - Faggi, Ana Maria (2011)
This briefing describes examples of integrated coastal zone management systems carried out along the Atlantic coastal strip in Argentina. The programmes helped to limit negative impacts and to regulate uses, applying adaptive management based on a holistic approach. This briefing forms part of the 'current trends in municipal engineering' series.